Integrated production of edible mushroom (Auricularia auricular-judae), fermentable sugar and solid biofuel. (June 2021) - Chen, Feng; Grimm, Alejandro; Eilertsen, Lill; Martín, Carlos; Arshadi, Mehrdad; Xiong, Shaojun
Abstract: This study aimed to develop an energy- and resource-efficient process for the coproduction of edible mushroom, fermentable sugar and solid biofuel from wood residues. A promising potential was revealed for wood ear fungus ( Auricularia auricular-judae ), which yielded about 200 g mushroom per kg dry birch-based substrate, with concomitant degradation of 76.8 and 85.7% of lignin and xylan, respectively, in the substrate. Substrate pasteurisation by hot-air (85–100 °C) was as effective as by energy intensive autoclaving (121 °C), resulting comparable mushroom growth and degradation of lignocellulose. The spent mushroom substrate (SMS) contained 28–33% glucan, which upon analytical enzymatic saccharification released around 46% of the potentially-achievable glucose, corresponding to a 2.3–fold enzymatic digestibility compared with that of the raw substrate. The solid leftover generated after enzymatic hydrolysis revealed high thermal energy value and promising combustion characteristics, showing a plausibility to be recycled as solid fuel for self-supporting energy system and space heating. Highlights: Wood residues have potential for coproduction of food, bioethanol and solid fuel. No difference between heat treatments (85–121 °C) on fungal yield and SMS compositions. Wood ear SMS resulted in 2.3 times higher glucan digestibility than raw substrate. Leftover from enzymatic hydrolysis showed promising combustion characteristics.